Low Specific Phosphorus Uptake Affinity of Epilithon in Three Oligo- to Mesotrophic Post-mining Lakes - Konopáčová, Eliška; Nedoma, Jiří; Čapková, Kateřina; Čapek, Petr; Znachor, Petr; Pouzar, Miloslav; Říha, Milan; Řeháková, Klára (Frontiers in Microbiology, 2021)
Epilithon contributes to phosphorus (P) cycling in lakes, but its P uptake traits have been rarely studied. We measured the chemical composition of epilithon and its inorganic P uptake kinetics using isotope 33P in three deep oligo- to mesotrophic post-mining lakes in April, July, and October 2019. Over the sampling period, epilithon biomass doubled, while the P content in biomass dropped to 60% of the April values and the seasonal changes in P content expressed per epilithon area were only marginal and statistically not significant. High epilithic C:P molar ratios (677 on average) suggested strong P deficiency in all investigated lakes. Regarding the kinetic parameters of phosphorus uptake, maximum uptake velocity (Vmax, seasonal range 0.91.9–101 129 mg P g OM–1 h–1) decreased by an order of magnitude from April to October, while half-saturation constant (KS, seasonal range 1.63.9–103 135 mg P L–1) did not show any consistent temporal trend. Values of epilithic specific P uptake affinity (SPUAE, seasonal range 0.081–2.23.1 L g OM–1 h–1) decreased from spring to autumn and were 2–4 orders of magnitude lower than the corresponding values for seston (SPUAsest), which showed opposite trend. Considering our results, we suggest a possible mechanism underlying a stable coexistence of planktonic and epilithic microorganisms, with plankton prospering mostly in summer and autumn and epilithon in winter and spring season. Additionally, a phenomenon of reversible abiotic P adsorption on epilithon was observed.